EVALUASI PEMBERIAN SANTUNAN PT. JASA RAHARJA(PERSERO) CABANG RIAU TERHADAP KORBAN KECELAKAAN LALU LINTAS JALAN - Ihcwani Ihcwani; Arief Rifa'i (UIR Press, 2018)
This study aims to determine the process of granting compensation to people who suffered a road traffic accident in PT. Riau Branch Services Raharja . Assessment indicators used include, Policy, Monitoring, Implementation. This type of research is located in Riau Branch PT. Services Raharja is using descriptive survey, which is to prioritize the list of the questionnaire as a data collection tool. And data collected by the tool is then used as the main raw material for analyzing the condition of objectivity existence empirical research goals that employees amounted to 6 people and society as many as 94 people. Samling two techniques used in determining the individual sample is census techniques for employees and purposive technique samling for people who receive compensation funds. Types and data collection techniques used consisted of primary data, the data collected by questionnaire and interview techniques as well as the secondary. Collected using observation techniques. While data analysis technique used is to use tools frequency table. Based on this analysis technique researchers assess and conclude that the administration of Benefit Evaluation Branch PT.Services Raharja Riau Against Road Traffic Accident Victims are less accomplished At intervals assessment. Recommendations should be considered especially with respect to improvement of the process of granting compensation to victims of road traffic accidents to improve the delivery of more effective and efficient compensation.